Case reportSecond salvage treatment for local recurrence of prostate cancer using high-dose-rate brachytherapy: a case report - Claren, Audrey; Gautier, Mathieu; Feuillade, Julien; Falk, Alexander Tuan; Levi, Jean-Michel Hannoun (Journal of Contemporary Brachytherapy, 2015)
Purpose: Currently, there are no recommendations for the management of a second local recurrence of prostate adenocarcinoma except for the introduction of androgen deprivation therapy (ADT). Case report: A 69-year-old man underwent a third salvage local treatment with high-dose-rate brachytherapy (HDRB), for a second biochemical relapse for local recurrence. Thirty-five Grays in 5 fractions were delivered on the whole prostate extended to the proximal part of left seminal vesicle. Given the availability of new treatment techniques in our radiation therapy department, a dosimetric comparison between HDRB and stereoatactic radiosurgery (SRS) was performed. Results: Immediate tolerance of HDRB was acceptable with achievement of prostate specific antigen (PSA) nadir in 24 months (0.03 ng/ml). Observed late toxicities were only grade 2 urinary incontinence. Dosimetric comparison showed a slight advantage on clinical target volume coverage and rectum protection for the SRS. The HDRB showed an advantage on bone irradiation including femoral heads and the volume receiving 0.5 Gy (EQD2 = 1 Gy with α/β = 3). Conclusions: A third local treatment with good tolerance could be a therapeutic option in case of a second local prostate cancer recurrence in order to delay, as long as possible, the chemical castration. Both techniques (HDRB and SRS) seem valid and should be chosen based on the availability and experience in a treatment center.